Investigating the Role of Google Translate in English Vocabulary Acquisition among Junior High School Students in the Digital Era - Ryan Putra Gemilang Ginting; Kresna Ningsih Manik; Siti Aisah Ginting (Pusat riset dan Inovasi Nasional, 2026)
This study investigates the role of Google Translate in supporting English vocabulary learning among junior high school students in the digital era. The research employs a qualitative approach involving seventh-grade students at SMP Negeri 19 Medan. Data were collected through pre-test and post-test, classroom observation, interviews, and documentation. The findings reveal that Google Translate significantly helps students understand vocabulary more quickly, improves their learning efficiency, and increases their confidence in completing English tasks. Students also demonstrate greater autonomy in exploring new vocabulary independently. However, the study also identifies challenges, particularly students’ tendency to rely excessively on direct translation without fully understanding context, which may lead to superficial learning. Therefore, teacher guidance is essential to ensure the effective and critical use of this tool. The study concludes that Google Translate can serve as a valuable learning resource when integrated appropriately into classroom instruction. The findings contribute to the development of technology-enhanced language learning and provide practical implications for teachers in utilizing digital tools effectively.